Research Progress of Traditional Chinese Medicine on Diarrhea-predominant Irritable Bowel Syndrome - Xuemei Yang; Hui Ding (Journal of Artificial Intelligence and Information, 2026)
Irritable bowel syndrome (IBS) is a common functional disorder of the digestive system, characterized by recurrent abdominal pain and bloating accompanied by changes in stool consistency and bowel habits. The symptoms often recur or persist and are difficult to resolve. In clinical practice, diarrhea-predominant irritable bowel syndrome (IBS-D) is the most common subtype. This article mainly reviews internal and external treatment methods of traditional Chinese medicine for this disease, summarizes their advantages and disadvantages, and aims to provide more effective therapeutic strategies for clinical practice.